2021
DOI: 10.1016/j.esmoop.2021.100131
|View full text |Cite
|
Sign up to set email alerts
|

Has COVID-19 had a greater impact on female than male oncologists? Results of the ESMO Women for Oncology (W4O) Survey

Abstract: Background: European Society for Medical Oncology Women for Oncology (ESMO W4O) research has previously shown under-representation of female oncologists in leadership roles. As early reports suggested disproportionate effects of the COVID-19 pandemic on women, the ESMO W4O Committee initiated a study on the impact of the pandemic on the lives of female and male oncologists. Methods: A questionnaire was sent to ESMO members and put on the ESMO website between 8 June 2020 and 2 July 2020. Questions focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…There is evidence that the pandemic has had an unequal impact on gender with female clinicians shouldering the greater burden of domestic responsibilities which may be exacerbating the pressure of growing professional demands. 14 , 15 In Survey II, we previously highlighted concerns raised regarding career development, training and job security disproportionately impacting trainee and early-career oncologists. 5 Survey III broadens these concerns to that of a more widespread impending crisis in workforce retention.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the pandemic has had an unequal impact on gender with female clinicians shouldering the greater burden of domestic responsibilities which may be exacerbating the pressure of growing professional demands. 14 , 15 In Survey II, we previously highlighted concerns raised regarding career development, training and job security disproportionately impacting trainee and early-career oncologists. 5 Survey III broadens these concerns to that of a more widespread impending crisis in workforce retention.…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing concern that the COVID-19 pandemic may have exacerbated these inequalities and widened the gender publishing gap, as women may have disproportionately shouldered the coexisting pandemic burdens of increased domestic responsibilities including educating children during school closures and providing care for young and elderly dependents,16–19 and the academic demands of adopting virtual clinical platforms, committee work, and teaching 19 20. The early impact of the COVID-19 pandemic remains to be investigated on publications and authorship in gynecologic oncology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study that looked at the impact of the pandemic on male and female oncologists found that in a sample of 541 oncologists, females were much more likely to report that the pandemic affected their professional career in a negative way (85%) when compared to males being asked the same question (76%). Women also reported that the COVID-19 pandemic affected their personal life (89% vs. 78% of men) and family life (84% vs. 77% of men) in negative ways and that they spent less time on science (39% vs. 25% of men) [ 60 ]. In order to design the best interventions and to truly address the components of mental health among oncology HCPs, gender will have to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…One longitudinal survey of 1269 oncologists from 104 countries found that almost half of the respondents (45%) reported not having enough time for their families as a result of the pandemic and that this phenomenon had increased substantially from the first time data were collected from this sample early in the pandemic (34.6%) [ 59 ]. Another study that looked at the impact of the pandemic on male and female oncologists found that in a sample of 541 oncologists, females reported that the COVID-19 pandemic affected their personal life (89% vs. 78% of men) and family life (84% vs. 77% of men) in negative ways [ 60 ]. Similarly, a study of Indian physicians that included surgical and medical oncologists found that female HCPs had increased domestic responsibilities such as household chores and were more likely to be responsible for managing their child’s education when compared to their male colleagues.…”
Section: Rapid Changes To the Nature Of Hcps’ Work And Day-to-day Livesmentioning
confidence: 99%